THE DIFFERENCE OF MEAN PLATELET VOLUME AND PLATELET COUNT IN CORONARY HEART DISEASE PATIENTS WITH ACUTE CORONARY SYNDROME AND NON ACUTE CORONARY SYNDROME - Aditya Paelo Rizki Sikumbang; Indranila Kustarini Samsuria; Novi Anggriyani; Charles Limantoro (Jurnal Kedokteran Diponegoro, 2021)
Background: Coronary Heart Disease (CHD) is currently one of main causes and the first death in developed and developing countries, including Indonesia. CHD appeared with the clinical appearance of asymptomatic, stable angina pectoris until acute coronary syndrome. ACS is a progressively CHD and takes parameters that describe the process pathogenesis. MPV and platelet count are two parameters in the complete blood count which reflect the activity of platelets in CHD.